Directors' defence of reliance on professional advisers under Anglo-Australian law. (March 2015) - Wan, Wai Yee
This paper analyses the issue of whether directors may use reliance on professional advice as a defence to a claim for breach of duty to exercise care, skill and diligence under common law or companies legislation in England and Australia. While England and Australia share the same common law tradition and have similar statutory provisions on the standard of care of directors, an English court generally regards a director as acting reasonably when he seeks advice from a qualified and independent professional adviser in a specialist matter within his expertise. In the absence of any conflict of interest, reliance is only unreasonable if the circumstances are so plain and obvious that no prudent person will rely on the advice. In contrast, recent Australian cases, particularly ASIC v Healey, ASIC v MacDonald and ASIC v Fortescue, restrict the circumstances in which directors can rely on professional advisers, even in specialist matters. This paper argues that the difference in approach between the two jurisdictions can be explained on two grounds. First, the Australian cases can be distinguished from the English cases because the former are special situations dealing with matters involving non-delegable duties of care imposed by legislation. Second, the potential outcomes of the breach of the duty of care differ in England and Australia, and this difference has a much deeper, substantive influence on the content of the standard of care. Contrary to academic suggestion, it is suggested that the Australian developments may not always be appropriate in determining the scope of the defence of reliance on professional advice in England.